2015
DOI: 10.1111/echo.13094
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Left Atrial Strain and Doppler Measurements with Invasive Measurement of Left Ventricular End‐Diastolic Pressure in Patients Stratified for Different Values of Ejection Fraction

Abstract: Background: This study aimed at exploring the correlation of left atrial longitudinal function by speckle tracking echocardiography (left atrial strain) and Doppler measurements (E/E' ratio) with direct measurements of left ventricular (LV) end-diastolic pressure (LVEDP) in patients stratified for different values of ejection fraction. Methods: The study population was 80 stable patients with sinus rhythm undergoing cardiac catheterization. This population was selected in order to have four groups of 20 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
126
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(160 citation statements)
references
References 27 publications
11
126
1
2
Order By: Relevance
“…Furthermore, peak LA strain was shown to correlate well with LV filling pressures in studies of patients with systolic HF, suggesting peak LA strain to be a potentially good noninvasive marker of elevated filling pressures (19,20). However peak LA strain is susceptible to the effects of age, obesity, valvular disease, such as mitral regurgitation, and atrial fibrillation, which we accounted for in this study by limiting our study population to patients with normal LVEF and no significant valvulopathy (21-23).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, peak LA strain was shown to correlate well with LV filling pressures in studies of patients with systolic HF, suggesting peak LA strain to be a potentially good noninvasive marker of elevated filling pressures (19,20). However peak LA strain is susceptible to the effects of age, obesity, valvular disease, such as mitral regurgitation, and atrial fibrillation, which we accounted for in this study by limiting our study population to patients with normal LVEF and no significant valvulopathy (21-23).…”
Section: Discussionmentioning
confidence: 97%
“…Compared with patients with normal diastolic function, patients with mild diastolic dysfunction had significantly reduced E sr and S sr but increased A sr. Another study (42) demonstrated that LA systolic strain (measured using STE) inversely correlated with LV end diastolic pressure. Similar to the E/E' ratio, LA systolic strain correlates with LV end diastolic pressure in patients with preserved or mildly reduced LVEF, whereas in patients with moderate or severe reduction of EF, E/E' correlated poorly and LA systolic strain provided a better estimation of LV filling pressures.…”
Section: Correlation Of La Strain With Diastolic Dysfunctionmentioning
confidence: 97%
“…In chronic conditions, LA volume and strain correlate with LV end‐diastolic pressures irrespective of EF 75, 76. Mechanical stress induces stretching and stiffening of the atria 77.…”
Section: Risk Factors and Pathophysiology Of Atrial Remodelling In Hementioning
confidence: 99%